Metabolic Changes of Active Components of Important Medicinal Plants on the basis of Traditional Chinese Medicine under Different Environmental Stresses - Shahrajabian, Mohamad H.; Kuang, Yue; Cui, Haoran; Fu, Lan; Sun, Wenli (Current Organic Chemistry, 2023)
Traditional Chinese medicine is an ancient system of wellness and health that has been used in almost all countries of the world, specially in Asia for thousands of years. The growth, development, final yield and chemical compounds of medicinal plants can be negatively influenced by different kinds of biotic and abiotic stresses. Abiotic stress signals are chemical stress (Mineral salts, heavy metal, aerosols, gaseous toxins, pesticides, and pollutants), salinity (salt), temperature (Heat, cold), radiation (Ionisation radiation, light and UV), water (Flooding, drought) and mechanical stress (Submergence, wind, soil movement). Relevant literature has been obtained using the keywords “Traditional Chinese Medicine”, “Abiotic Stress”, “Biotic Stress”, “Ginseng”, “Ginger”, “Goji berry”, “Astragalus”, “Ginkgo”, “Artemisia annua L.”, “LC-MS”, “GC-MS”, and “NMR” in scientific information, namely “Web of Science”, “PubMed”, “SciFinder”, and “Elsevier”. Some of the plants’ secondary metabolites under different growth conditions are Camptothecin (Camptotheca acuminata), Capsaicin (Capsicum sp.), Rosmarinic acid (Salvia miltiorrhiza), Codeine (Papaver somniferum), Resveratrol (Grapes, groundnut), Artemisinin (Artemesia annua), Allicin (Allium sativum), Rohitukine (Dysoxylum binectariferum), Stevioside (Stevia rebaudiana), Andrographolide (Andrographis paniculata), Saikosaponins (Bupleurum chinense), Sennosides (Cassia augustifolia), Rutin (Dimorphandra mollis), Valepotriates (Valeria species), Indole alkaloids (Catharanthus roseous), and Furanocoumarins (Bituminaria bituminosa). The aim of this article is a survey of active chemical compounds and metabolic changes of some of the most important medicinal plants in traditional Chinese medicine (TCM) in both abiotic and biotic stresses. Future research is needed to evaluate the effects of biotic and abiotic stresses on chemical compounds and active metabolites of medicinal plants specially traditional Chinese medicine, and more surveys on the roles of LC-MS, GC-MS and NMR techniques for a better understanding of chemical components of medicinal plants.
Keywords: astragalus